Improvement of Thermal Cycling Resistance of AlxSi1−xN Coatings on Cu Substrates by Optimizing Al/Si Ratio - Panin A. V. Alexey Viktorovich; Shugurov A. R. Artur Rubinovich; Kazachenok M. S. Marina Sergeevna; Sergeev V. P. Viktor Petrovich (2019, 2019)
Title screen